Isolation of Potential Plant Growth Promoting Rhizobacteria (PGPR) from Cassava (Manihot esculenta) Rhizosphere Soil - Suri Raihan Safriani; Lenni Fitri; Yulia Sari Ismail (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Cassava is the third most important calorie source in tropical area after rice and corn. The microorganism associated with cassava roots may be potent and useful for application to promote plant growth. Plant growth promoting rhizobacteriaÂ is a group of benefical bacteria that live in rhizosphere. The aim of this study was to isolate and to identify the potential Plant Growth Promoting Rhizobacteria (PGPR) from cassava rhizosphere soil. The study consisted of isolation and identification of bacteria based on morphological and biochemical characters, hypersensitive reaction test, the ability to solubilize potassium and phosphate, and the ability to inhibit the growth of pathogen Sclerotium rolfsii. A total of nine bacteria isolates were succesfully isolated from Cassava rhizosphere soil. Those isolates suspected as Micrococcus sp.1, Micrococcus sp.2, Micrococcus sp.3, Micrococcus sp.4, Micrococcus sp.5, Micrococcus sp.6, Neisseria sp.1, Neisseria sp.2 and Bacillus sp. All nine isolates did not show hypersensitivity reactions. Only Neisseria sp.1 and Neisseria sp. 2 were able to solubilize potassium and phosphate. All isolates were able to inhibit the growth of S. rolfsii. The highest inhibition was done by Micrococcus sp.4 (51.46 %). The physical and chemical properties of cassava rhizosphere soil affected the type of bacteria found in this study. The result confirmed that the potential isolates obtained from cassava rhizosphere soil can be plant growth promoters. The present study suggested that PGPR isolates might have potential in future field applications as plant growth promoters or biocontrol agents.